Targeting Filamin A Reduces Macrophage Activity and Atherosclerosis. Issue 1 (2nd July 2019) - Bandaru, Sashidar; Ala, Chandu; Salimi, Reza; Akula, Murali K.; Ekstrand, Matias; Devarakonda, Sravani; Karlsson, Joakim; Van den Eynden, Jimmy; Bergström, Göran; Larsson, Erik; Levin, Max; Borén, Jan; et al.
Abstract : Background: The actin-binding protein FLNA (filamin A) regulates signal transduction important for cell locomotion, but the role of macrophage-specific FLNA during atherogenesis has not been explored. Methods: We analyzed FLNA expression in human carotid atherosclerotic plaques by immunofluorescence. We also produced mice with Flna -deficient macrophages by breeding conditional Flna -knockout mice ( Flna o/fl ) with mice expressing Cre from the macrophage-specific lysosome M promoter ( LC ). Atherosclerosis in vivo was studied by transplanting bone marrow from male Flna o/fl / LC mice to atherogenic low-density lipoprotein receptor–deficient ( Ldlr –/– ) mice; and by infecting Flna o/fl and Flna o/fl / LC mice with AdPCSK9 (adenoviral vector overexpressing proprotein convertase subtilisin/kexin type 9). Furthermore, C57BL/6 mice were infected with AdPCSK9 and then treated with the calpain inhibitor calpeptin to inhibit FLNA cleavage. Results: We found that macrophage FLNA expression was higher in advanced than in intermediate human atherosclerotic plaques. Flna o/fl / LC macrophages proliferated and migrated less than controls; expressed lower levels of phosphorylated AKT and ERK1/2; exhibited reduced foam cell formation and lipid uptake; and excreted more lipids. The deficiency of Flna in macrophages markedly reduced the size of aortic atherosclerotic plaques in both Ldlr –/–BMT: Flnao/fl/LC and AdPCSK9-infected Flna o/fl / LC mice. Intima/media ratios and numbers of CD68-positive macrophages in atherosclerotic plaques were lower in Flna -deficient mice than in control mice. Moreover, we found that STAT3 interacts with a calpain-cleaved carboxyl-terminal fragment of FLNA. Inhibiting calpain-mediated FLNA cleavage with calpeptin in macrophages reduced nuclear levels of phosphorylated STAT3, interleukin 6 secretion, foam cell formation, and lipid uptake. Finally, calpeptin treatment reduced the size of atherosclerotic plaques in C57BL/6 mice infected with AdPCSK9. Conclusions: Genetic inactivation of Flna and chemical inhibition of calpain-dependent cleavage of FLNA impaired macrophage signaling and function, and reduced atherosclerosis in mice, suggesting that drugs targeting FLNA may be useful in the treatment of atherosclerosis. Abstract : Supplemental Digital Content is available in the text.